Tatak Pilipino [episode no. 70] [videorecording]. ([Quezon City ABS-CBN], 1992)
A unique display of Pilipino ways and style.
Arinola (5 min.) -- Bella Flores (15 min.) -- Sirena-Dyesebel (5 min.) -- Sugal (10 min.) -- Porta Vaga's Nuestra Senora de Soledad in Cavite (15 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Flores, Bella; Soledad, Nuestra Senora de (Porta Vga, Cavite).; Bedpans -- Philippines; Gambling -- Philippines; Sociology; Actors and actresses